Whole‐organ transdermal photobiomodulation (PBM) of COVID‐19: A 50‐patient case study. Issue 2 (22nd November 2021) - Williams, Richard K.; Raimondo, John; Cahn, David; Williams, Aldon; Schell, Daniel
Abstract: A nonrandomized 50‐person case study of COVID‐19‐positive patients was conducted employing (for the first time) a regimen of whole‐organ deep‐tissue transdermal dynamic photobiomodulation (PBM) as a primary (or exclusive) therapeutic modality in the treatment of coronavirus. Therapy sessions comprised algorithmically alternating red (650 nm) and near‐infrared (NIR; 850 nm) LEDs with an average irradiance of 11 mW/cm 2 dynamically sequenced at multiple pulse frequencies. Delivered via 3D bendable polymeric pads maintaining orthogonal optical incidence to body contours over 1, 000 cm 2, a single 84‐minute session concurrently delivered 20 kJ to the sinuses and 15 kJ to each lung at skin temperatures below 42°C. Therapeutic outcomes observed include significant reductions in the duration and severity of disease symptoms. Acute conditions including fever, body aches (BA) and respiratory distress comprising paroxysmal coughing; lung congestion, dyspnea and hypoxia; sinus congestion; acute eye inflammation; and extreme malaise were eliminated in 41/50 patients within 4 days of commencing PBM treatments with 50/50 patients fully recovering within 3 weeks with no supplemental oxygen requirements. SpO2 concentrations improved as much as 9 points (average 2.5 points) across the entire study population. The PBM sessions required to completely resolve COVID‐19 conditions appears monotonically correlated to the time‐to‐treatment (TTTx)—the delay between the onset of a patient's symptoms and commencing PBM therapy. In contrast, acute inflammatory symptoms were resolved within 4 days irrespective of TTTx. Abstract : In a 2020 nonrandomized outpatient case study, 50 symptomatic COVID‐19‐positive patients received noninvasive deep‐tissue whole‐organ PBM therapy comprising 84‐minute concurrent anterior treatments of lungs and sinuses using red and NIR LEDs pulsed in multifrequency algorithms. After two sessions, therapeutic outcomes showed acute symptomatic relief of paroxysmal coughing; lung congestion dyspnea; and hypoxia; and sinus inflammation in 82% of the study irrespective of initial severity and 3‐week full recovery for all patients.